2018
DOI: 10.1002/jctb.5586
|View full text |Cite
|
Sign up to set email alerts
|

Selenate removal in biofilm systems: effect of nitrate and sulfate on selenium removal efficiency, biofilm structure and microbial community

Abstract: BACKGROUND: Selenium (Se) discharged into natural waterbodies can accumulate over time and have negative impacts on the environment. Se-laden wastewater streams can be treated using biological processes. However, the presence of other electron acceptors in wastewater, such as nitrate (NO 3-) and sulfate (SO 4 2-), can influence selenate (SeO 4 2-) reduction and impact the efficiency of biological treatment systems. RESULTS: SeO 4 2removal by biofilms formed from an anaerobic sludge inoculum w ∘ as investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…As shown in Figure 5, R1 and R2 had very different community structures that changed with either electron-acceptor or -donor availability. Despite lack of NO 3 − , the abundant genera in R1 were DB Methyloversatilis, Denitratisoma, and Dechloromonas (Tan, Espinosa-Ortiz, et al, 2018). Also present was the SRB Desulfovibrio and the fermenting bacterium Propionivibrio (Okabe et al, 2003).…”
Section: Microbial Biofilms Diversity Ecological Indexes and Community Structurementioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 5, R1 and R2 had very different community structures that changed with either electron-acceptor or -donor availability. Despite lack of NO 3 − , the abundant genera in R1 were DB Methyloversatilis, Denitratisoma, and Dechloromonas (Tan, Espinosa-Ortiz, et al, 2018). Also present was the SRB Desulfovibrio and the fermenting bacterium Propionivibrio (Okabe et al, 2003).…”
Section: Microbial Biofilms Diversity Ecological Indexes and Community Structurementioning
confidence: 99%
“…DB, SRB, and SeRB can co-exist (Subedi et al, 2017), which introduces the possibility of competition, such as for a common electron donor. Having simultaneously available NO 3 − , SO 4 2− , and SeO 4 2− as electron acceptors often can lead to competition among microbial groups (particularly when NO 3 − and SeO 4 2− are present together; Lai et al, 2014Lai et al, , 2016 or even inhibition of one microbial process (Shi et al, 2020 (Shi et al, 2020), SO 4 2− favored SeO 4 2− reduction (Tan, Espinosa-Ortiz, et al, 2018), or no effect was seen (Oremland et al, 1989). Furthermore, some studies reported that SeO 4 2− reduction can occur along with NO 3 − and SO 4 2− reductions at a Se:N:S molar ratio of 1:40:100 (Tan et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, characterization using high-end microscopic and spectroscopic techniques revealed the formation of biogenic Se (0)-Te(0) nanostructures, entrapped in the sludge granules, during simultaneous reduction of Se and Te oxyanions (Wadgaonkar et al, 2018c , individually, on Se removal in continuous operation, a correlation with different reactor configurations, microbial growth system, and co-oxyanions was observed. SO 4 2− was shown to be a controlling factor in biofilm systems using a drip flow reactor (DFR) (Tan et al, 2018a) and biotrickling filter (BTF) (Tan et al, 2018c) achieving both higher Se removal and more biofilm growth/formation when SO 4 2− was present. In contrast, the UASB reactor did not reveal any changes, either increase or decrease, in Se removal efficiencies, when SO 4 2− was removed from (Tan et al, 2018d) or included (Tan et al, 2018c) in the feed solution.…”
Section: Presence Of Telluriummentioning
confidence: 99%
“…SeO 4 2− reduction can be carried out by various microorganisms including denitrifiers and sulfate reducers. The microbial community analysis revealed the presence of high relative abundances of denitrifiers along with a small proportion of sulfate reducers, irrespective of the presence of NO 3 − (Tan et al, 2018a(Tan et al, , 2018d (DeMoll-Decker & Macy, 1993;Nancharaiah & Lens, 2015a). It was hypothesized that the presence of NO 3 − can promote a higher state of metabolic activity in microorganisms (Oremland et al, 1999).…”
Section: Presence Of Telluriummentioning
confidence: 99%
“…To reduce selenate at very low concentrations, a fixed-bed biofilm reactor (FBBR) might be more suitable from the engineering point of view than a suspended growth reactor because it is designed to prevent microbial washout while keeping the biocatalysts, i.e., selenate reducing bacteria, in the system longer. Moreover, the potential of biofilm reactors can be extended via a long acclimation period [12], which can simultaneously reduce selenate and other anions, such as nitrate and perchlorate, even in diluted agricultural or coal-mining drainage [13]. However, such simultaneous reductions make it difficult to rationalize how the microbial acclimation affects selenate reduction with other oxyanions and how the carbon and energy source limitations alter the reduction of selenate and other oxyanions in the biofilm reactor.…”
Section: Introductionmentioning
confidence: 99%